An update in the utilization of N-acetyl cysteine & vitamin c for tackling the oxidative stress in acute kidney injury secondary to robust sepsis - A systematic review - Kaur, Kulvinder Kochar; Allahbadia, Gautam; Singh, Mandeep (Journal of Clinical Nephrology, 2022)
The commonest etiology of acute kidney injury (AKI) is Sepsis that results in an escalation of morbidity and mortality in the hospital intensive care units. Existentially, the therapy of septic AKI rather than being definitive or curative is just supportive, without tackling the pathophysiology. Usually, Sepsis gets correlated with systemic inflammation, along with the escalated generation of Reactive oxygen species (ROS), in particular superoxide. Simultaneously liberation of nitric oxide (NO) subsequently reacts with the superoxide, thus, resulting in the generation of reactive nitrogen species (RNS), that is mostly peroxynitrite. This sepsis stimulated generation of ROS in addition to RNS might cause a reduction in the bioavailability of NO that modulates microcirculation aberrations, localized tissue hypoxia as well as mitochondrial impairment, thus starting a vicious cycle of cellular damage which results in AKI. Here we conducted a systematic review utilizing search engine PubMed, Google scholar; Web of science; Embase; Cochrane review library utilizing the MeSH terms like septic AKI; ROS; inducible nitric oxide synthase (iNOS); nicotinamide adenine nucleotide phosphate(NADPH)oxidase complex; Oxidative stress; Renal medullary hypoxia; Hypoxia inducible factor1; hypoxia responsive enhancer A; mitochondrial impairment; Intrarenal oxygenation; urinary oxygenation; erythropoietin gene; RRT; NAC; Vitamin C from 1950 to 2021 till date. We found a total of 6500 articles out of which we selected 110 articles for this review. No meta-analysis was done. Thus here we detail the different sources of ROS, at the time of sepsis, besides their pathophysiological crosstalk with the immune system, microcirculation as well as mitochondria that can result in the generation of AKI. Furthermore, we detail the therapeutic utility of N-acetylcysteine (NAC), besides the reasons for its success in ovine as well as porcine models of AKI. Moreover, we discuss preclinical along with clinical for evaluation of Vitamin C’s antioxidant effects as well as pleiotropic effects as a stress hormone that might aid in abrogation of septic AKI.